Efficiency of Capital-Labor in Nigeria’s Mining Sector: A Cobb-Douglas Framework - Ogujiuba, Kanayo; ., Nancy Stiegler (Journal of Economics and Behavioral Studies, 2014)
The productivity in the Nigeria’s mining sector presents significance challenges, especially in view of its prospect in diversifying the national economy. The need to uncover the efficiency by way of estimating two major production functions (i.e. capital and labor) cannot be minimized. However, this paper uses econometric technique to estimates the Cobb-Douglas production function of mining sector between 1980 and 2011 periods in Nigeria. To avoid a spurious series, unit root test was conducted based on Augmented Dickey-Fuller (ADF) to test for the stationarity or otherwise of the variables in the model. The outcome reveals that the substitution parameters α and β (substitution parameters for capital and labor) confirms the a priori expectation that the pair of α and β are positive values. Despite labor is the most significant factor of production, the study also found that other inputs such as innovations and technology are positively significant in this period of modern mining production processes in view of the global economic outlook. The study amongst others recommends strong political will of government, transparency and accountability to drive efficient and effective mining sector reform, increased capital investment in innovations, technology, and raw materials.